The Effect of Black Pepper (Piperine) Extract Supplementation on Growth Performance, Nutrient Digestibility, Fecal Microbial, Fecal Gas Emission, and Meat Quality of Finishing Pigs - Sampath, Vetriselvi (Animals (Basel), 2020)
SIMPLE SUMMARY: Recently, Livestock industries use many herbs and spices as feed additives for various purposes. In addition, herbal extracts can be efficiently used as growth promoters, anti-stress agents, Immune boosters, and antimicrobials. However, limited studies have been conducted to evaluate the effect of black pepper extract (BPE) in swine diets. So, in this study, we use different doses of BPE (piperine) as supplemental additives to evaluate the growth performance of finishing pigs. The findings suggested that the graded level of BPE supplementation in pigs diet had a positive effect on growth performance, nutrient digestibility, fecal microbial, fecal gas emission, and meat quality. The results of this research will provide a new perception on the applications of BPE as a feed additive in livestock feed industry. ABSTRACT: The study was conducted to assess the effect of black pepper extract (BPE) supplementation on the growth performance, nutrient digestibility, fecal microbial, fecal gas emission, and meat quality of finishing pigs. A total of 180 crossbred [(Landrace × Yorkshire) × Duroc] finishing pigs with average initial body weight (BW) of 53.7 ± 1.42 kg were used in 10-week trial and allotted to 6 dietary treatments (6 replications pens/treatment with 5 pigs per pen). The dietary treatments were: CON (basal diet), TRT1-CON + 0.025% BPE, TRT2-CON + 0.05% BPE, TRT3-CON + 0.1% BPE, TRT4-CON + 0.2% BPE, TRT5-CON + 0.4% BPE. Linear increase in body weight gain (BWG) (p = 0.038, 0.006) and average daily gain (ADG) were observed (p = 0.035, 0.007,and 0.006 respectively), during the overall trial in pigs fed increasing levels of BPE in supplemented diet compared to control. The dietary supplementation of BPE showed a linear increase (p = 0.007) in gain-to-feed ratio (G:F) at week 10. However, there were no significant results observed on average daily feed intake (ADFI) during the overall experiment. The total tract digestibility of dry matter (DM) was linearly improved (p = 0.053) with graded levels of BPE. In addition, BPE diet supplementation had linearly increased fecal Lactobacillus counts (p = 0.048) and decreased Escherichia coli counts (p = 0.031) in pigs at week 10. Furthermore, NH3, methyl mercaptans, and acetic acid was linearly decreased (p = 0.023, 0.056, 0.054) in pigs fed graded level of BPE supplementation. The inclusion of BPE in pigs’ diet had linearly increased (p = 0.015) backfat thickness at week 10. Thus, we concluded that BPE supplementation had positively enhanced the growth performance, nutrient digestibility, fecal microbial, fecal gas emission, and meat quality of finishing pigs.